Robot‐assisted versus open radical cystectomy: A cohort study on perioperative outcomes accounting for stage selection bias and surgical experience. Issue 4 (5th May 2021) - Zeuschner, Philip; Linxweiler, Johannes; Mohr, Rebecca; van Heemskerk, Sara; Wagenpfeil, Gudrun; Wagenpfeil, Stefan; Ohlmann, Carsten; Siemer, Stefan; Stöckle, Michael; Saar, Matthias
Abstract: Background: Most comparisons of robot‐assisted (RARC) versus open radical cystectomy (ORC) for urothelial carcinoma do not factor the inherent stage selection bias or surgical experience. Methods: We compared the perioperative outcomes of 229 RARC and 335 ORC at a single tertiary referral centre with propensity score matching and multiple regression models, when controlling for tumour and patient characteristics, surgeon's experience and type of urinary diversion. Results: RARC had less major complications (19.8% vs. 34.1%) and ICU admissions (6.6% vs. 19.8%), with lower blood loss (400 vs. 500 ml) and transfusion rates. The operating time was longer (336 vs. 286 min), but decreased with surgeon's experience. RARC had less positive surgical margins (3% vs. 8.4%) and a higher lymph node count (14 vs. 11). Conclusions: In this large single centre series comparing RARC with ORC controlling for stage selection bias and surgical experience, RARC proved significantly better outcomes, especially with intracorporeal urinary diversion.